Preparation method of functional polyacrylic acid alkyl ester latex and ASA (Acrylonitrile Styrene Acrylate) resin

By preparing functional polyalkyl acrylate latex with low internal crosslinking and high external crosslinking structure, the problems of morphological stability and mechanical properties of ASA resin after multiple processing are solved, and excellent impact resistance and long-term mechanical properties are achieved.

CN119569954AActive Publication Date: 2025-03-07WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411746693.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

It is difficult for existing ASA resins to maintain excellent rubber morphological stability under strict multi-cycle processing conditions, resulting in a gradual decrease in mechanical properties after multiple processing.

Method used

By preparing functional polyalkyl acrylate latex with low internal crosslinking and high external crosslinking structure, the difference in the degree of crosslinking of the rubber particles is controlled to maintain shape integrity under external force impact and high shear environment.

Benefits of technology

The ASA resin can maintain excellent impact resistance and long-term retention of mechanical properties after multiple processing, avoiding the disintegration of rubber particles and degradation of performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163915440000061
    Figure BDA0005163915440000061
  • Figure BDA0005163915440000062
    Figure BDA0005163915440000062
  • Figure BDA0005163915440000071
    Figure BDA0005163915440000071
Patent Text Reader

Abstract

The invention provides a preparation method of functional polyacrylic acid alkyl ester latex and ASA (Acrylonitrile Styrene Acrylate) resin. By controlling the difference of the double-layer crosslinking degree of the functional polyacrylic acid alkyl ester latex, the prepared rubber has excellent shape retention; furthermore, the ASA resin prepared from the functional polyacrylic acid alkyl ester latex prepared by the preparation method disclosed by the invention has excellent impact resistance and excellent impact resistance retention after repeated processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymers, and in particular relates to a method for preparing a functional polyalkyl acrylate latex and the prepared ASA resin. Background Art

[0002] ASA (Acrylate-Styrene-Acrylonitrile) latex is an emulsion obtained by grafting a layer of styrene and acrylonitrile copolymer (SAN) on the surface of polyacrylate latex through an emulsion grafting reaction. After condensation and drying, ASA high-rubber powder is obtained. The product of melt blending of ASA high-rubber powder and SAN resin is ASA resin. ASA resin is a material with excellent performance, excellent weather resistance, oxidation resistance, good mechanical properties and coloring properties, high electrical insulation, corrosion resistance and oil resistance, etc. It is widely used in the fields of automobiles, building materials, electronic products, etc., and has huge market potential.

[0003] PCR (post-consumer recycled material) recycled plastic is a plastic material recycled and reused from post-consumer plastic products, which can be remade into plastic raw materials after processing. It is environmentally sustainable, price-competitive and has broad application prospects, and is an effective solution to the problem of plastic waste. As society's requirements for environmental protection become higher and higher, ASA manufacturers have also begun to pay attention to the performance degradation of ASA resin after PCR cycling. Due to the lack of cross-linking in the rubber phase of ASA resin, the rubber particles of the prepared ASA resin are prone to disintegration under strong shear conditions such as extrusion and injection molding, and then lose their toughening effect. Patent CN115636904A is prepared by stirring deionized water, acrylate monomer, emulsifier, cross-linking agent and initiator until completely dissolved, and then heating to 55-75°C under nitrogen for reaction for 0.5-2h; adding acrylate monomer, emulsifier, cross-linking agent and initiator to obtain polyacrylate latex; then adding deionized water, chelating agent, reducing agent, reducing agent and initiator, In a nitrogen environment, the temperature is raised to 50-75°C; styrene monomer, acrylonitrile monomer and initiator are then added dropwise, and the temperature is raised to 75°C for 1-2 hours to obtain a large-particle ASA latex, and then a high-impact ASA resin is prepared; Patent CN109651571A uses a cross-linked urethane polymer containing acrylate groups as a seed, and then coats it with acrylate rubber, and then grafts styrene-acrylonitrile to obtain an ASA graft copolymer with good impact properties; Authorized patent CN112867742B prepares a polystyrene latex The hard-shell polyacrylic acid alkyl ester rubber particles of the type have a higher shape retention degree, but due to the compatibility difference between the styrene polymer and the alkyl acrylate polymer, phase separation is easy to occur under hot melting and high shear, so the shape is bound to be difficult to maintain after multiple processing; Patent CN116574351A uses a polymer agglomerating agent to agglomerate small-particle polyacrylate latex into a large-particle polyacrylate latex, then constructs a mantle structure on the surface of the large-particle polyacrylate latex, and performs emulsion graft polymerization to form a core-shell AS A graft copolymer is used to obtain ASA resin. Based on the characteristics of the typical particles of the agglomeration process, small particles are agglomerated into large particles. The rubber particles are physically entangled in the form of molecular chains. The rubber particles are bound to disintegrate easily under harsh environments. Patent CN115677946A prepares a six-core-shell structure of acrylate-styrene-acrylonitrile graft copolymer. The structure of the rubber core is very easy to deform, which is not conducive to the shape retention after multiple processing. In addition, the process requires six polymerization reactions, and the preparation process is cumbersome, which will seriously damage the production efficiency in the later stage. It can be seen that although the above methods can obtain ASA resins with higher impact strength, none of them mentions a technical method that can effectively solve the problem of ASA resin maintaining excellent rubber morphology stability under harsh multi-cycle processing conditions. Therefore, it is of great practical significance to study and prepare a high-impact strength ASA resin composition that still has high particle morphology retention after multiple processing. Summary of the invention

[0004] One object of the present invention is to provide a method for preparing a functional polyalkyl acrylate latex and an ASA resin prepared therefrom. The functional polyalkyl acrylate latex (B) prepared by the present invention has a structure of "low internal crosslinking and high external crosslinking". The low internal crosslinking makes it easy for PBA rubber particles dispersed in a matrix SAN resin to deform when subjected to external impact, thereby facilitating the formation of stress concentration points and effectively forming cavities to absorb energy, thereby making the resin have excellent impact resistance. The PBA rubber outer layer has the characteristic of high crosslinking, making the rubber outer layer similar to a body structure, thereby greatly enhancing the shape retention ability of the rubber particles when subjected to an external harsh high shear environment, and preventing particle disintegration after multiple melt processing of the resin, and maintaining the mechanical properties for a long time.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0006] A method for preparing a functional polyalkyl acrylate latex comprises the following steps:

[0007] (1) adding deionized water, alkyl acrylate, functional monomer, emulsifier, electrolyte, initiator and chain transfer agent into a reaction kettle for emulsion polymerization, and obtaining a rubber core (A) when the polymerization conversion rate of alkyl acrylate and functional monomer is 96%-99.5%;

[0008] (2) adding a mixture of alkyl acrylate, functional monomer, emulsifier, initiator and chain transfer agent to the product of step (1) to continue the reaction, and when the polymerization conversion rate of alkyl acrylate and functional monomer is 96%-99.5%, a functional polyalkyl acrylate latex (B) is obtained.

[0009] The mass ratio q / Q of the amount q of the functional monomer added in step (1) to the amount Q of the alkyl acrylate added is: 0≤q / Q≤3%; the mass ratio g / G of the amount g of the functional monomer added in step (2) to the amount G of the alkyl acrylate added is: 1%≤g / G≤5%.

[0010] The basis of the polymerization conversion rate in step (2) includes the alkyl acrylate and the functional monomer in step (1) and step (2).

[0011] As a preferred solution, the mass dosage of each component in step (1) is as follows:

[0012] 100-120 parts of deionized water, preferably 105-115 parts;

[0013] 2-6 parts of alkyl acrylate, preferably 3-5 parts;

[0014] Functional monomer 0-0.06 parts, preferably 0.01-0.05 parts;

[0015] Emulsifier 0.01-0.1 parts, preferably 0.03-0.08 parts;

[0016] Electrolyte 0.1-0.5 parts, preferably 0.2-0.4 parts;

[0017] Initiator 0.05-0.5 parts, preferably 0.2-0.4 parts;

[0018] Chain transfer agent 0-0.5 parts, preferably 0-0.3 parts.

[0019] As a preferred solution, the mass dosage of each component in step (2) is as follows:

[0020] 30-50 parts of deionized water, preferably 35-45 parts;

[0021] Alkyl acrylate 94-98 parts, preferably 95-97 parts;

[0022] Functional monomer 0.98-4.7 parts, preferably 1.92-4.1 parts;

[0023] Emulsifier 0.1-3 parts, preferably 1.1-2.0 parts;

[0024] Initiator 0.05-1.0 part, preferably 0.2-0.7 part;

[0025] Chain transfer agent 0-0.5 parts, preferably 0-0.3 parts.

[0026] In one embodiment of the present invention, the alkyl acrylate is an alkyl acrylate with an alkyl chain length of C1-C15, preferably one or more selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylbutyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, heptyl acrylate, n-pentyl acrylate and lauryl acrylate, more preferably an alkyl acrylate with an alkyl chain length of C1-C4, and further preferably butyl acrylate.

[0027] In one embodiment of the present invention, the functional monomer is a polymerizable monomer having multiple olefin double bonds, preferably one or more selected from divinylbenzene, ethylene glycol dimethacrylate, triallyl isocyanurate, dicyclopentadienyl acrylate, and allyl methacrylate.

[0028] In one embodiment of the present invention, the emulsifier is selected from one or more of potassium oleate, potassium rosinate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl allyl sulfosuccinate, dipotassium C16-C18 alkenyl succinate and dioctyl sodium sulfosuccinate.

[0029] In one embodiment of the present invention, the electrolyte is selected from one or more of potassium carbonate, sodium carbonate, potassium bicarbonate, sodium bicarbonate, sodium phosphate, sodium pyrophosphate, potassium pyrophosphate, and sodium tripolyphosphate.

[0030] In one embodiment of the present invention, the initiator is selected from inorganic peroxides, preferably one or more of hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate.

[0031] In one embodiment of the present invention, the chain transfer agent is an alkyl mercaptan with a main carbon chain length of C8-C14, selected from one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, primary octyl mercaptan, secondary octyl mercaptan and tert-octyl mercaptan.

[0032] In one embodiment of the present invention, the polymerization temperatures of step (1) and step (2) may be the same or different, and preferably the polymerization temperature is 50-80°C.

[0033] According to another aspect of the present invention, an ASA resin is provided, wherein the ASA resin is prepared by comprising the functional polyalkyl acrylate latex (B) prepared by the present invention.

[0034] In the present invention, the prepared functional polyalkyl acrylate latex is grafted, coagulated, filtered, and dried to obtain polymer powder, and then mechanically blended with styrene acrylonitrile copolymer (SAN resin), melt granulated to obtain ASA resin, and injection molded to obtain test specimens. This is a conventional technique in the art, and the specific operating details can be manipulated according to the methods involved in "ABS Resin and Its Applications" written by Huang Liben et al., which will not be repeated here.

[0035] The present invention controls the difference in the degree of double-layer crosslinking of the functional polyalkyl acrylate latex, so that the prepared rubber has excellent shape retention, and further the ASA resin prepared from the functional polyalkyl acrylate latex (B) prepared by the present invention has excellent impact resistance and excellent impact resistance retention after multiple processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the SEM of the resin after initial processing in Example 1;

[0037] Figure 2 This is the SEM of the resin in Example 1 after 5 processing;

[0038] Figure 3 This is the SEM of the resin after initial processing in Comparative Example 1;

[0039] Figure 4 This is the SEM of the resin in comparative example 1 after 5 processings.

[0040] Specific implementation method

[0041] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the examples, but the content of the present invention is not limited to the following examples. If the source of raw materials in the following examples and comparative examples of the present invention is not specifically stated, the raw materials used in the examples or comparative examples are all obtained from commercial channels.

[0042] According to the present invention, the polymerization conversion rate of alkyl acrylate and functional monomer is tested by the following method: 0.05g sample is taken into a 20ml headspace bottle, diluted to 1.00g with DMF, and the sample is analyzed by gas chromatograph to obtain the content of residual alkyl acrylate and functional monomer. The test result is put into the following formula to calculate the polymerization conversion rate of alkyl acrylate and functional monomer:

[0043]

[0044] Example 1: Preparation of functional alkyl acrylate latex B1

[0045] (1) 110 kg of deionized water, 2 kg of n-butyl acrylate, 0.01 kg of sodium dodecyl sulfate, 0.1 kg of potassium carbonate, 0.05 kg of potassium persulfate and 0.1 kg of tert-dodecyl mercaptan were added to a reactor and stirred. Nitrogen was introduced into the reactor to a temperature of 100 kPa and then evacuated to 8 kPa. The oxygen in the reactor was removed repeatedly. The reactor was heated to 50° C. to start the reaction. The conversion rate was controlled to be 96%;

[0046] (2) The temperature of the reactor was adjusted to 80° C., and a mixture emulsion consisting of 30 kg of deionized water, 94 kg of n-butyl acrylate, 0.98 kg of dicyclopentadienyl acrylate, 1.1 kg of sodium dodecyl sulfate, 1 kg of potassium persulfate, and 0.25 kg of tert-dodecyl mercaptan was continuously fed into the reactor to continue the reaction. When the polymerization conversion rate reached 99%, the reaction was stopped, the temperature was lowered, and the material was discharged to obtain a functional alkyl acrylate latex B1. The q / Q value of the prepared functional alkyl acrylate latex B1 was 0%, and the g / G value was 1%.

[0047] Example 2-5: Preparation of functional alkyl acrylate latex B2-B5

[0048] The conditions of Examples 2-5 and Example 1 are shown in Table 1, and the reaction steps refer to Example 1.

[0049] Table 1

[0050]

[0051]

[0052] Comparative Example 1 Preparation of alkyl acrylate latex D1

[0053] All the materials added in Example 1 are added into the reactor at once before the reaction starts, and then the reaction is carried out according to the reaction temperature of step (2) in Example 1. After the conversion rate of step (2) in Example 1 is reached, the temperature is lowered to stop the reaction, thereby obtaining alkyl acrylate latex D1.

[0054] Comparative Example 2 Preparation of alkyl acrylate latex D2

[0055] The process of Example 2 was repeated, except that the amount of divinylbenzene added in step (1) was increased to 0.08 kg and the amount of allyl methacrylate added in step (2) was increased to 5.64 kg. The remaining raw materials, experimental conditions and reaction steps were the same as those in Example 2.

[0056] Compared with the functional alkyl acrylate latex B2 prepared in Example 2, the q / Q value of the latex D2 prepared in this comparative example is designed to be 4%, and the g / G value is designed to be 6%.

[0057] Comparative Example 3 Preparation of alkyl acrylate latex D3

[0058] The process of Example 2 was repeated, except that the amount of allyl methacrylate added in step (2) was reduced to 0.49 kg, and the other raw materials, experimental conditions and reaction steps were the same as those of Example 2. Compared with the functional alkyl acrylate latex B2 prepared in Example 2, the designed value of q / Q of the latex D3 prepared in this comparative example remained unchanged, but the value of g / G was designed to be 0.5%.

[0059] The parameters of Comparative Examples 1-3 are shown in Table 2.

[0060] Table 2 Parameters of Comparative Examples 1-3

[0061]

[0062] Using the polyalkyl acrylate latex prepared in Examples 1-5 and Comparative Examples 1-3, ASA resin was prepared in the following manner.

[0063] 1) Preparation of ASA grafted latex

[0064] 60 kg (in terms of solid content) of the polyalkyl acrylate latex prepared by Examples 1-5 and Comparative Examples 1-3, 120 kg of deionized water, 0.001 kg of FeSO4·7H2O, 0.01 kg of sodium pyrophosphate, and 0.1 kg of glucose were added to the reactor respectively and stirring was started. After the reactor was heated to 70° C., a mixed pre-emulsion consisting of 0.2 kg of cumene hydroperoxide, 30 kg of styrene, 10 kg of acrylonitrile, 0.5 kg of tert-dodecyl mercaptan, 3 kg of potassium oleate and 10 kg of deionized water was continuously added to the reactor for 3 hours. After the feeding was completed, the reactor was heated to 80° C. and the reaction was continued for 3 hours. The reactor was cooled to room temperature and stirring was stopped, and the ASA grafted latex was obtained by filtration.

[0065] 2) Preparation of ASA rubber powder

[0066] Add 1.2 kg of concentrated sulfuric acid and 200 kg of deionized water into the coagulation kettle and start stirring to fully dissolve the concentrated sulfuric acid. Heat the coagulation kettle to 75° C. and add 100 kg of the ASA grafted latex prepared in step 1) into the coagulation kettle in a continuous feeding manner for 1 hour. After the feeding is completed, heat the coagulation kettle to 90° C. and keep it warm for 1 hour. Cool the coagulation kettle to room temperature and filter, wash and dehydrate the coagulation slurry to obtain ASA wet rubber powder. Dry the ASA wet rubber powder at 65° C. in a fluidized bed dryer to a water content of <1% to obtain ASA rubber powder.

[0067] 3) ASA resin preparation, injection molding and performance testing

[0068] A twin-screw extruder is used at 200°C-220°C, LG Chemical brand 80HF SAN resin is used as the blending continuous phase, and the ASA rubber powder prepared in step 2) is used as the blending dispersed phase. The ASA resin is obtained by blending, extruding and granulating according to the polyalkyl acrylate rubber content of 27%.

[0069] In order to evaluate the rubber morphology and performance retention of the above ASA resin under multi-cycle processing conditions, the above ASA resin was extruded for multiple cycles under the same blending conditions, and the changes in impact strength were compared.

[0070] The ASA resin extruded through multiple cycles was used to prepare test specimens on an injection molding machine at 190° C. The impact strength of the resin was tested according to ASTM D256 standard. The specific results are shown in Table 3.

[0071] Table 3 Impact strength of ASA resins prepared in Examples 1-5 and Comparative Examples 1-3 and performance retention after multiple processing

[0072]

[0073]

[0074] It can be seen from Table 3 above that, unlike Comparative Examples 1-3, Examples 1-5 of the present invention control the difference in the degree of double-layer crosslinking of the functional polyalkyl acrylate latex, so that the ASA resin prepared by the functional polyalkyl acrylate latex (B) prepared by the present invention has excellent impact resistance and impact resistance retention after multiple processing. The four kinds of resin particles prepared by Example 1 and Comparative Example 1, initially and after 5 times of processing, were respectively dissolved and dispersed in acetone, and observed using a PRISMA E SEM scanning electron microscope from Thermo Fisher Scientific, focusing on the shape integrity of the rubber particles, as shown in the attached figure. Figure 1 and 2 It is shown that the rubber particles of the ASA resin prepared by Example 1 still have a complete spherical morphology after 5 processing cycles. Figure 3 and 4 It is shown that most of the rubber particles of the ASA resin prepared in Comparative Example 1 disintegrate after 5 processing cycles. The above can be used as a theoretical basis for the preparation scheme of the functional alkyl acrylate latex provided by the present invention to solve the problem of the impact resistance retention of the ASA resin after multiple processing.

[0075] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a functional polyalkyl acrylate latex, comprising the following steps: (1) adding deionized water, alkyl acrylate, functional monomer, emulsifier, electrolyte, initiator and chain transfer agent into a reaction kettle for emulsion polymerization, and obtaining a rubber core (A) when the polymerization conversion rate of alkyl acrylate and functional monomer is 96%-99.5%; (2) adding a mixture of alkyl acrylate, functional monomer, emulsifier, initiator and chain transfer agent to the product of step (1) to continue the reaction, and when the polymerization conversion rate of alkyl acrylate and functional monomer is 96%-99.5%, a functional polyalkyl acrylate latex (B) is obtained.

2. The method according to claim 1, characterized in that: The mass ratio q / Q of the added amount q of the functional monomer to the added amount Q of the alkyl acrylate in step (1) is: 0≤q / Q≤3%; the mass ratio g / G of the added amount g of the functional monomer to the added amount G of the alkyl acrylate in step (2) is: 1%≤g / G≤5%.

3. The method according to claim 1 or 2, characterized in that: The mass dosage of each component in the step (1) is as follows: 100-120 parts of deionized water, preferably 105-115 parts; 2-6 parts of alkyl acrylate, preferably 3-5 parts; Functional monomer 0-0.06 parts, preferably 0.01-0.05 parts; Emulsifier 0.01-0.1 parts, preferably 0.03-0.08 parts; Electrolyte 0.1-0.5 parts, preferably 0.2-0.4 parts; Initiator 0.05-0.5 parts, preferably 0.2-0.4 parts; Chain transfer agent 0-0.5 parts, preferably 0-0.3 parts.

4. The method according to any one of claims 1 to 3, characterized in that: Step (2) The mass dosage of each component is as follows: 30-50 parts of deionized water, preferably 35-45 parts; Alkyl acrylate 94-98 parts, preferably 95-97 parts; Functional monomer 0.98-4.7 parts, preferably 1.92-4.1 parts; Emulsifier 0.1-3 parts, preferably 1.1-2.0 parts; Initiator 0.05-1.0 part, preferably 0.2-0.7 part; Chain transfer agent 0-0.5 parts, preferably 0-0.3 parts.

5. The method according to any one of claims 1 to 4, characterized in that: The alkyl acrylate is an alkyl acrylate with an alkyl chain length of C1-C15, preferably one or more selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylbutyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, heptyl acrylate, n-pentyl acrylate and lauryl acrylate, more preferably an alkyl acrylate with an alkyl chain length of C1-C4, and further preferably butyl acrylate.

6. The method according to any one of claims 1 to 5, characterized in that: The electrolyte is selected from a mixture of one or more of potassium carbonate, sodium carbonate, potassium bicarbonate, sodium bicarbonate, sodium phosphate, sodium pyrophosphate, potassium pyrophosphate, and sodium tripolyphosphate.

7. The method according to any one of claims 1 to 6, characterized in that: The emulsifier is selected from one or more of potassium oleate, potassium rosinate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl allyl sulfosuccinate, dipotassium C16-C18 alkenyl succinate and dioctyl sodium sulfosuccinate.

8. The method according to any one of claims 1 to 7, characterized in that: The chain transfer agent is an alkyl mercaptan with a main carbon chain length of C8-C14, selected from one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, primary octyl mercaptan, secondary octyl mercaptan and tert-octyl mercaptan.

9. The method according to any one of claims 1 to 8, characterized in that: The polymerization temperatures of step (1) and step (2) may be the same or different, and preferably the polymerization temperature is 50-80°C.

10. An ASA resin, prepared by comprising a functional polyalkyl acrylate latex prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High impact ASA graft copolymer and synthetic method

    CN109651571A

  • Polyacrylate grafted rubber copolymer and thermoplastic molding composition

    CN112867742B

  • ASA graft copolymer having superior shock resistance, weather resistance, coloring properties, and method for manufacturing same

    CN104066757A

  • Preparation method of polybutadiene latex and prepared ABS (Acrylonitrile Butadiene Styrene) resin

    CN116355150A

  • Silicon-containing acrylate-styrene-acrylonitrile core-shell graft copolymer and preparation method thereof

    CN118221941A

Cited By

  • ASA (Acrylonitrile Styrene Acrylate) material with multi-layer structure and preparation method thereof

    CN122255375A